Analysis of Distribution and Consumption Patterns in Pangkalpinang City - Suhaidar Suhaidar; M. Afdal Samsuddin; Nurwasya Nurwasya; Ria Atlantika (Universitas Bangka Belitung, 2024)
The food industry not only fulfils basic human needs for survival, but is also one of the vital economic sectors for a region. It creates jobs, from farmers to distributors, and drives various related industries such as packaging and transportation. Furthermore, the export of food products can be a significant source of foreign exchange. Thus, the healthy and sustainable development of the food industry not only ensures the food security of the community, but also contributes to economic growth and overall regional welfare. The purpose of this study is to analyze distribution and consumption patterns in Pangkalpinang City, using analysis of market structure detection, and analysis of trade and transport margins. The data from this study uses primary data, the results show that the distribution pattern of cooking oil and chicken eggs has the longest path and the pattern of consumption of food commodities contributing to the highest deflation is rice